2017
DOI: 10.1155/2017/5792192
|View full text |Cite
|
Sign up to set email alerts
|

Growth on Alpha-Ketoglutarate Increases Oxidative Stress Resistance in the YeastSaccharomyces cerevisiae

Abstract: Alpha-ketoglutarate (AKG) is an important intermediate in cell metabolism, linking anabolic and catabolic processes. The effect of exogenous AKG on stress resistance in S. cerevisiae cells was studied. The growth on AKG increased resistance of yeast cells to stresses, but the effects depended on AKG concentration and type of stressor. Wild-type yeast cells grown on AKG were more resistant to hydrogen peroxide, menadione, and transition metal ions (Fe2+ and Cu2+) but not to ethanol and heat stress as compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Earlier, we examined the effects of different AKG concentrations on yeast growth in the YPD medium and oxidative stress resistance of exponentially growing yeast cells [ 10 ]. We found that at the concentration of 10 mM AKG had no effect on yeast growth but it enhanced endogenous antioxidant defense and increased yeast resistance to oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, we examined the effects of different AKG concentrations on yeast growth in the YPD medium and oxidative stress resistance of exponentially growing yeast cells [ 10 ]. We found that at the concentration of 10 mM AKG had no effect on yeast growth but it enhanced endogenous antioxidant defense and increased yeast resistance to oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-ketoglutarate (AKG) is an important intermediate of many metabolic processes combining catabolic and anabolic functions. Our previous results show that the supplementation with AKG did not affect growth of S. cerevisiae YPH250 strain (wild type) in glucose-containing medium starting from inoculation to 72 h of cultivation [ 10 ]. Here, we demonstrated that AKG supplementation had no effect on total cell number in YPH250 cultures during a 15-day cultivation period ( Figure 1(a) ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saccharomyces cerevisiae , it has been described that growth in the presence of 2‐OG protects cells against the stress caused by H 2 O 2 and other oxidants; however, this protection disappears in mutants lacking some antioxidant enzymes such as catalases or superoxide dismutases. Taking this into account, the effect is partially attributed to a role of 2‐OG in the induction of defence systems against oxidative stress (Bayliak et al ., ). By contrast, in the case of Synechocystis , the protective effect of 2‐OG is also observed in the ∆ katG mutant, lacking the main enzyme involved in the defence against H 2 O 2 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…One of the parameters indicative of ROS homeostasis that increases in Saccharomyces in the presence of 2-OG is glutathione reductase activity (GR), the enzyme responsible for regenerating oxidized glutathione (Bayliak et al, 2017). However, Synechocystis lacks this enzyme (Narainsamy et al, 2013), so the possible mechanism involved in the reduction of oxidized glutathione is unknown, despite the fact that an essential role of reduced glutathione in the protection against ROS has been shown in this cyanobacterium (Cameron & Pakrasi, 2010).…”
Section: Discussionmentioning
confidence: 99%